Agmatine: clinical applications after 100 years in translation - ARICIOĞLU, FEYZA (ELSEVIER SCI LTD, 2013)
Agmatine (decarboxylated arginine) has been known as a natural product for over 100 years, but its biosynthesis in humans was left unexplored owing to long-standing controversy. Only recently has the demonstration of agmatine biosynthesis in mammals revived research, indicating its exceptional modulatory action at multiple molecular targets, including neurotransmitter systems, nitric oxide (NO) synthesis and polyamine metabolism, thus providing bases for broad therapeutic applications. This timely review, a concerted effort by 16 independent research groups, draws attention to the substantial preclinical and initial clinical evidence, and highlights challenges and opportunities, for the use of agmatine in treating a spectrum of complex diseases with unmet therapeutic needs, including diabetes mellitus, neurotrauma and neurodegenerative diseases, opioid addiction, mood disorders, cognitive disorders and cancer.
Keywords: NITRIC-OXIDE SYNTHASE; CLONIDINE-DISPLACING SUBSTANCE; PREFRONTAL CORTICAL MORPHOLOGY; POLYAMINE STRESS-RESPONSE; ALTERS RAT HIPPOCAMPAL; ARGININE DECARBOXYLASE; IMIDAZOLINE RECEPTORS; ENDOGENOUS LIGAND; METABOLIC PATHWAY; OPIOID ANALGESIA